Brain-based Criteria of Human Death. Study of the Issue - Norkowski, Jacek (Studia Theologica Varsaviensia, 2020)
In this article I first tried to demonstrate that the theory of so-called brain death is unsustainable from a scientific point of view. +e data that the medical profession provides on this subject clearly contradicts such a theory. It is impossible to prove, on the basis of the knowledge available to this science that people who are in a state of cerebral death are really dead. +e only thing that the doctor can say, without exceeding the limits of the discipline he represents, is that these people have a significant degree of brain damage. +is does not mean, however, that the brain is so damaged that is has ceased to perform all its functions. On the contrary, these patients usually show many symptoms of brain activity. Recognition of these sick people as dead, therefore, contradicts the principles of the medical art. +e acceptance of the theory of so-called brain death has also given rise to many problems from the legal point of view. Recognition as a living or deceased person depends on the criteria for brain death, which vary from country to country. +e law has therefore become arbitrary in such an important area as human life and death. +e adoption of the theory of brain death on the basis of such un-robust scientific criteria has undoubtedly become possible only through the acceptance of certain philosophical assumptions that reduce the human to his or her consciousness. A permanent loss of consciousness was de facto considered to be evidence of human death. +is position contradicts the achievements of Christian thought in the field of philosophical anthropology, which emphasises the unity of the individual and the importance of his or her bodily aspect. What is even more important, however, is the fact that modern man tends to think in terms of moral utilitarianism. Many people believe that it is possible to sacrifice the life of a person who is seriously ill and who has no hope of improvement (in this case, a person with cerebral death syndrome) for the benefit of other patients. +is attitude explains the passivity of many circles and the failure to discuss such an important issue as the rightness or wrongness of the theory of so-called brain death. It is not without significance that there is a specific transplant lobby in individual countries, which puts moral pressure on entire societies to accept the removal of organs for transplantation from people who are in a state of so-called brain death, and suppresses the discussion of moral problems associated with it. It is necessary for the Catholic Church to develop a clear position on this matter. +is has not yet happened. +ere is even a surprising lack of consensus among various the authorities. However, some of the hierarchy of the Catholic Church have already spoken on this matter. +ese include Cardinal Meissner, Archbishop of Cologne, who clearly rejected the theory of brain death as incompatible with the principles of the Church’s teaching8'. Pope John Paul II also wrote in the encyclical Evangelium Vitae: “Nor can we remain silent about the existence of other, better camouflaged but no less dangerous forms of euthanasia. We would be dealing with them, for example, if, in order to obtain moreorgans for transplantation, we proceeded to collect these organs from donors before they were declared dead according to objective and adequate criteria.” Although these words do not mention the concept of brain death, they refer to it indirectly. +is paper was written in order to draw attention to just such a moral problem hidden in the concept of so-called brain death. In conclusion, I would like to give the floor to one of the participants in the discussion on brain death, Dr Tomoko Abe. She wrote: “It is true that the latest developments in science and technology have brought many benefits. At the same time, however, they have brought unprecedented confusion in philosophy and culture to our societies. Due to the destructive tendencies of the present day, it is becoming increasingly important to establish social standards to protect the most vulnerable members of society, such as young children and unconscious patients who cannot defend themselves. We therefore conclude that the current diagnostic criteria for brain death should be abolished and that a worldwide ban on transplants from people with cerebral death syndrome should be introduced.”88 Dr. Abe is not alone in a desire to overthrow the theory of so-called brain death and to consider its criteria as non-scientific. +e same is demanded by many other authors. +e voice of the Catholic Church in this matter is undoubtedly one of the most important. As the greatest authority in the world in matters of morality and human rights, it cannot fail to explain the issue of so-called brain death in its teaching.